2019
DOI: 10.3390/ani9121105
|View full text |Cite
|
Sign up to set email alerts
|

Neutering Effects on Social Behaviour of Urban Unowned Free-Roaming Domestic Cats

Abstract: The “trap, spay/neuter, and release” programs to manage unowned free-roaming cat populations are diffused worldwide and they are largely advised even in countries where the suppression of unowned cats is enforced by law. Despite the massive neutering campaigns in the world, there is little information on the influence of neutering on individual cat behaviour, as well as on the social structure of cat colonies. The aim of this study is to verify such effects. Before neutering, the group consisted of 17 free-roa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
1
17
1
1
Order By: Relevance
“…Unspecified generalisation about the relationship between sex and aggressivity, without considering factors such as neuter status, context (such as target of the behaviour) alongside the motivational-emotional status of the problem should therefore be treated with caution. Neutering has been reported to have a calming effect on behaviour with a decrease in aggression in both, males and females (44,52); by contrast our initial results indicated aggressivity was consistently highest in female neutered cats, and greater in females compared to males. This might reflect the management of male entire cats, who are perhaps kept away from other cats to reduce the chances of unplanned breeding, but deserves further attention, as this would not account for the generally lower aggression in neutered males compared to females.…”
Section: Discussioncontrasting
confidence: 87%
“…Unspecified generalisation about the relationship between sex and aggressivity, without considering factors such as neuter status, context (such as target of the behaviour) alongside the motivational-emotional status of the problem should therefore be treated with caution. Neutering has been reported to have a calming effect on behaviour with a decrease in aggression in both, males and females (44,52); by contrast our initial results indicated aggressivity was consistently highest in female neutered cats, and greater in females compared to males. This might reflect the management of male entire cats, who are perhaps kept away from other cats to reduce the chances of unplanned breeding, but deserves further attention, as this would not account for the generally lower aggression in neutered males compared to females.…”
Section: Discussioncontrasting
confidence: 87%
“…Using our IFA approach, we detected a significantly higher seroprevalence of FeMV-2 in male cats. This might be explained by the lack of neutering in this cohort, resulting in closer and more frequent social contacts between animals, increased roaming distance, urine spraying, and sexual activity [ 22 , 23 ]. Like for FeMV-2, the seroprevalence of feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV)' as well as 'canine distemper virus (CDV) have also been reported to be higher in male cats [ 24 ].…”
mentioning
confidence: 99%
“…In ocelots, visits to the latrines were more frequent during the reproductive period (King et al., 2017). In domestic cats, urine marking decreased or disappeared completely in males after neutering (Cafazzo et al., 2019), which showed the testosterone influence of this conduct (Tarttelin et al., 1998). Hence, testosterone levels seem to be related to marking behaviour in cats, being important for pheromonal signalling (Tarttelin et al., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In ocelots, visits to the latrines were more frequent during the reproductive period (King et al, 2017). In domestic cats, urine marking decreased or disappeared completely in males after neutering (Cafazzo et al, 2019), which showed the testosterone influence of this conduct (Tarttelin et al, 1998 Note<del author="Ana Piñeiro" command="Delete" timestamp="1603725681927" title="Deleted by Ana Piñeiro on 26/10/2020 12:21:21" class="reU3">s</del>: Differences in mean oestradiol metabolite levels (ng/g dry faeces) in European wildcat scats depending on the month of the year. Differences in mean progesterone metabolite levels (ng/g dry faeces) in European wildcat scats depending on the month of the year.…”
Section: Furthermore Low Oestradiol Levels During the Months Of Febrmentioning
confidence: 99%